Les Misérables Hugoliens et la Fatalité dans Les Misérables et Notre-Dame de Paris de Victor Hugo - Abdulhussein, Halah Zaid; Nasif, Majed Jamil (جامعة بغداد - كلية الآداب, 2019)
تظهر هاتان الرواياتان، البؤساء وأحدب نوتردام، موضوع دراستنا، المثالية الروائية حيث تقدم مشاهد متنوعة في وقت واحد كونها مشاهد واقعية ورومانسية وسياسية وتاريخية وتحملان موضوعات حقيقية من خلال الأماكن الرمزية والشخصيات التي جعلت من خلال هذه الروايات مظاهر شعبية واجتماعية. تتركز رواية أحدب نوتردام حول أحداث مؤلمة مستندة على أحداث تاريخية من العصور الوسطى وهذه الرواية تبين الفكر الاجتماعي والإنساني في تلك الحقبة. أما رواية البؤساء فإن الأحداث تدور في إطار اجتماعي في القرن التاسع عشر ومرتبطة بمعركة واترلو وأحداث الشغب في حزيران 1838، فشخصياتها تشهد البؤس الاجتماعي وهي رموز لضحايا منبوذين من الحياة الاجتماعية. لقد تجسد الوجهان الإنساني والوحشي في هاتين الروايتين تحت تأثير الظروف التي تحيط المرحلتين والتي تعاني منها الشخصيات؛ كالعبودية والاضطهاد والظلم الاجتماعي والفقر، كما ظهر هذان الوجهان من خلال الطبيعة الإنسانية والوحشية. لقد دفعت كل هذه المعاناة الشخصيات إلى النهاية التراجيدية كضحايا للظروف القاسية اجتماعيا وإنسانيا في تلك الحقبة.
The two novels of the study show the novelistic idealism that represents various scenes simultaneously; realistic, romantic, historical, and political scenes that have authentic topics via the symbolic places and characters that the novels used as popular and social aspects. The Hunchback of Notre-Dame revolves around tragic events that are based on medieval historic happenings. The novel explores the social and humanitarian ideology in that period of time. In The Miserables, the events of the novel take place in a social frame during the nineteenth century where the story is related to the battle of Waterloo and the acts of riot that happened in June 1838. The characters of the novel witness social misery and are symbols of the victims among the outcasts of social life. The humanitarian and monstrous sides in the two novels were revealed, under the influence of the two stages the characters are going though, in the form of slavery, oppression, social injustice, and poverty. Those two sides were also shown through the human and monstrous. All this suffering had led the characters to a tragic end as the victims of cruel social and human conditions in that era.
Keywords: النقد الأدبى -- رواية البؤساء -- رواية أحدب نوتردام